Współczesne tabu językowe, czyli o czym nie mówią Polacy - Rogodzińska, Katarzyna; Obrębska, Monika (Człowiek i Społeczeństwo, 2018)
The issue of contemporary linguistic taboo seems to be an important one due to the fact that we deal with its consequences in scientific, as well as social and educational, discourse. However, it has not been explored extensively enough. This thesis aims to investigate the differences in lexical processing of taboo and neutral words. The data was collected in a two-steps procedure. Firstly, a questionnaire was used to examine what topics are considered to be taboo in different age groups. Secondly, a psychological experiment was conducted with use of E-Prime programme in order to investigate the difference in taboo and neutral words reaction time. 58 people participated in the experiment, divided into two age groups. No statistically significant differences were observed between taboo and neutral words reaction time. However, it was proven that the taboo words reaction time is, in fact, statistically significantly longer for people in middle adulthood stage than for students. This study considers emotional valence as the only factor distinguishing taboo words from neutral words. In the future, to enable more precise words selection, the study should consider other lexical properties of the words as well.